Critical discourse analysis in teaching reading - Elok Putri Nimasari (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2016)
In Indonesian context, it is mostly found that reading material and its exercises examine of what have been explicitly discussed. Critical thinking is less introduced within reading texts and somehow it makes the students less understandable to know what is exactly meant by the author. However, when the students are able to think critically, they will also be able to connect between ideas and to solve the problems with logical reasons. From this reason, it is clearly seen that critical thinking should be introduced, for instance, through reading texts and its exercises. This article aims to present one idea that can be used to raise critical thinking by implementing a critical discourse analysis. Therefore, the relevant literature of teaching reading, CDA, the description of how the material is integrated with CDA and the teaching sequence will be described. It is expected that this article will have deeper insight and significant implication for some educational parties such as teachers and lecturers.